Separability of local reactivity descriptors - Tanwar, A; Pal, S (Journal of Chemical Sciences, 2005)
The size-dependence of different local reactivity descriptors of dimer A(2) and AB type of systems is discussed. We derive analytic results of these descriptors calculated using finite difference approximation. In particular, we studied Fukui functions, relative electrophilicity and relative nucleophilicity, local softness and local philicity. The results are explained using the example of the dimer of BH3NH3.
Keywords: condensed Fukai functions; Local reactivity descriptors; molecular interactions; separability

Molecular determinant for specificity: differential interaction of alpha-amylases with their proteinaceous inhibitors - Rane, Ashwini S.; Joshi, Rakesh S.; Giri, Ashok P. (Biochimica Et Biophysica Acta-General Subjects, 2020)
Background: alpha-Amylase inhibitors (alpha-AIs) belong to the discrete classes, and exhibited differential specificities against alpha-amylases from various sources. Several alpha-amylases and their complexes with inhibitors at the molecular level have been studied in detail. Interestingly, some alpha-AIs depict specific and selective interactions amid different insect alpha-amylases. Scope of review: There are studies to understand evolutionary variability and functional differentiation of insect alpha-amylases and their cognate inhibitors. We have examined sequence, structural, and interaction diversity between various alpha-amylases and alpha-AIs. Based on these analyses, we are providing a potential basis for the functional differentiation among certain insect a-amylases concerning mammalian counterparts and their interactions with different proteinaceous alpha-AIs. Major conclusions: Insect alpha-amylases have conserved domain architecture with differences in length, number of disulfide bonds, and secondary structure. Furthermore, few of them exhibit variable characteristics like chloride dependent activity, the presence of N-terminal glutamine residue to protect against proteolytic degradation, and loop variations near the enzyme active site. Conformation of alpha-AI protein could be an essential factor for their specificity and binding affinities towards target alpha-amylase(s). Furthermore, variation into the enzyme binding pocket residues might contribute to differential interactions with inhibitors. General significance: Molecular insights in the interactions between insect alpha-amylases and plant alpha-AI will provide the details of mechanisms assisting the inhibitor specificity. Furthermore, this information will help to design potent and effective alpha-AIs against specific alpha-amylase.
Keywords: Active site; alpha-amylase; alpha-amylase inhibitor; Insect; molecular interactions